(untitled) (TAMADDUN NURI JURNALI, 2025)
Each ethnic group, nation has its own independent, unique and inimitable rituals. One of them is the tradition of naming. Traditions and the order of naming a child among the Iranians of Bukhara are based on centuries-old historical and cultural heritage. In the article, from an ethnographic point of view, various rites of birth and naming children of the Iranians of the Bukhara oasis are analyzed and studied